Lactoperoxidase-mediated degradation of single-walled carbon nanotubes in the presence of pulmonary surfactant. (September 2015) - Bhattacharya, Kunal; El-Sayed, Ramy; Andón, Fernando T.; Mukherjee, Sourav P.; Gregory, Joshua; Li, Hu; Zhao, Yinchen; Seo, Wanji; Fornara, Andrea; Brandner, Birgit; Toprak, Muhammet S.; Leifer, Klaus; et al.
Abstract: Carbon nanotubes (CNTs) may elicit inflammatory responses following pulmonary exposure. Conversely, enzymatic biodegradation of CNTs by inflammatory cells has also been reported. The aim of this study was to study the degradation of oxidized single-walled CNTs (ox-SWCNTs) by lactoperoxidase (LPO), a secreted peroxidase present in the airways, and whether pulmonary surfactant affects this biodegradation. To this end, ox-SWCNTs were incubated in vitro with recombinant bovine LPO + H2 O2  + NaSCN in the presence and absence of porcine lung surfactant (Curosurf®) and biodegradation was monitored using UV–Vis–NIR spectroscopy, Raman spectroscopy, and scanning electron microscopy. The interaction of recombinant LPO with bundles of ox-SWCNTs was confirmed by atomic force microscopy. Cell-free biodegradation of ox-SWCNTs was also observed ex vivo in murine bronchoalveolar lavage fluid in the presence of H2 O2  + NaSCN. Our study provides evidence for biodegradation of ox-SWCNTs with a lung surfactant 'bio-corona' and expands the repertoire of mammalian peroxidases capable of biodegradation of ox-SWCNTs. These findings are relevant to inhalation exposure to these materials, as LPO serves as an important component of the airway defense system.